Extramedullary Plasmacytoma of the Larynx: A Case Report of Subglottic Localization - Jaqueline Ramírez-Anguiano; Hugo Lara-Sánchez; Deborah Martínez-Baños; Braulio Martínez-Benítez (Case Reports in Otolaryngology)
Extramedullary plasmacytoma (EMP) is a rare neoplasm of plasma cells, described in soft tissue outside the bone marrow. EMP of the larynx represents 0.04 to 0.45% of malignant tumors of the larynx. A male of 57 years old presented with hoarseness, dyspnea, and biphasic stridor of 2 months. The indirect laryngoscopy (IL) revealed severe edema of the posterior commissure and a polypoid mass in the right posterior lateral subglottic wall. A biopsy of the subglottic mass was performed by a direct laryngoscopy (DL). The histopathologic diagnosis was EMP CD138+, therefore radiotherapy was given at 54 Gy in 30 sessions. The patient had an adequate postoperative clinical course and a new biopsy was performed having tumor-free margins. All laryngeal lesions should be biopsied prior to treatment to determine an accurate diagnosis to guide a proper management of the condition. Radiation therapy to the EMP is considered the treatment of choice, having local control rates of 80% to 100%. The subglottis is the least accessible area of view and the least frequent location of a laryngeal mass, nevertheless the otolaryngologist should always do a complete and systematic exam of the larynx when a tumor is suspected, to detect diagnoses such as a subglottic plasmacytoma.